2013
DOI: 10.1177/1065912913509306
|View full text |Cite|
|
Sign up to set email alerts
|

Electoral Turnout and State Redistribution

Abstract: This study explores the relationship between electoral participation and income redistribution by way of social transfers, using data from the European Social Survey, the Comparative Study of Electoral Systems, and the Luxembourg Income Study. It extends previous research by measuring the income skew of turnout rather than using average turnout as a proxy for its income bias. We find that, controlling for a number of other variables, the income skew of turnout is negatively related to transfer redistribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Analysing data from the Luxembourg Income Study, Mahler () shows that a number of different measures of redistribution of income through taxation and transfers are strongly associated with voter turnout (cf. Kenworthy and Pontusson : 459–62).…”
Section: Electoral Mobilizationmentioning
confidence: 99%
“…Analysing data from the Luxembourg Income Study, Mahler () shows that a number of different measures of redistribution of income through taxation and transfers are strongly associated with voter turnout (cf. Kenworthy and Pontusson : 459–62).…”
Section: Electoral Mobilizationmentioning
confidence: 99%
“…104 For example, Larcinese 2007;Mahler 2008;Mahler et al 2014. 105 Notice that my results are not consistent with the expectations of the other (non-conditional) alternative approaches discussed above (e.g., power resource and insurance approaches) since I find that more inequality is associated with more redistribution.…”
Section: Discussion Of the Control Variablesmentioning
confidence: 99%
“…81 For example, Kenworthy and Pontusson 2005;Larcinese 2007;Mahler 2008;Mahler et al 2014. 82 Taken from the Penn World Tables.…”
Section: Datamentioning
confidence: 99%
“…An analysis of cross-national surveys conducted across wealthy, industrialized, democratic nations found that greater economic inequality is associated with lower interest in the issues being discussed by politicians, lower frequency of political discussion, and decreased voting by the non-wealthy [108]. Voter turnout in the US lags behind most other OECD nations [109,110] and participation in elections is strongly related to income and education level [111,112]. Low-income constituents are also less likely than high-income constituents to donate to political campaigns, volunteer for campaigns, or send letters or emails to elected officials [113].…”
Section: Inequality As a Threat To Democracymentioning
confidence: 99%